Effect of Traditional Chinese Medicine ointment rubbing therapy in the treatment of primary dysmenorrheal (中药膏摩治疗原发性痛经疗效观察) - CAO Lei (曹蕾); ZHANG Lijun (张丽君); KONG Xiaochun (孔晓春); CHEN Hong (陈宏) (Association of Integrative Nursing, 2022)
Objective To investigate the effect of rubbing therapy with Traditional Chinese Medicine (TCM) ointment in the treatment of primary dysmenorrheal. Methods Totally 82 patients with primary dysmenorrheal were randomly divided into the treatment group and control group, with 41 cases in each group. All patients received Shaofu Zhuyu Decoction, and an additional therapy of TCM ointment rubbing was carried out in the treatment group. The pain degree was evaluated by Visual Analogue Scale (VAS), and the effect of intervention was compared between two groups. Results The VAS score dropped in both two groups after treatment, and the VAS score in the treatment group was lower than that in the control group (P＜0. 01). The total effective rate was 90. 24%(37/41)in the treatment group, which was significant higher than 75. 61%(31/41)in the control group (P＜0. 05). Conclusion The rubbing therapy with TCM ointment is effective in pain relief in patients with primary dysmenorrheal. (目的 探讨运用中医护理技术中药膏摩疗法治疗原发性痛经的效果。方法 82例原发性痛经患者随机分为治疗组和对照组, 各41例。对照组给予少腹逐瘀汤治疗, 治疗组在对照组基础上增加中药膏摩疗法。采用视觉模拟自评量表(VAS)评估患者痛经疼痛程度, 比较两组干预效果。结果 治疗后两组VAS评分均较治疗前降低, 且治疗组VAS 评分低于对照组, 差异有统计学意义(P＜0. 01)。对照组总有效率75. 61%(31/41), 低于治疗组的90. 24%(37/41), 差异有统计学意义(P＜0. 05)。结论 中药膏摩疗法能进一步减轻痛经患者的疼痛程度。)